Variations in Observations of Geosynchronous Magnetopause and Last Closed Drift Shell Crossings With Magnetic Local Time. Issue 8 (17th August 2022) - Daggitt, Thomas A.; Horne, Richard B.; Glauert, Sarah A.; Del Zanna, Giulio; Freeman, Mervyn P.
Abstract: We analyze a set of events in which both electron flux dropouts caused by magnetopause shadowing and geosynchronous magnetopause crossings (GMCs) are observed. These observations are compared to event‐specific last closed drift shell (LCDS) models derived from the TS05 and TS07 external field models and magnetopause standoff distance. The LCDS models show good association with losses due to magnetopause shadowing but fail to reproduce observations of GMCs on the timescale of minutes. We show that different satellites in geostationary orbit observe different trends in electron flux during storm events on timescales of less than a day due to their separation in longitude. These differences demonstrate that both satellite L * and magnetic local time must be taken into account when modeling rapid variations in the outer radiation belt, and at least three satellites in geostationary orbit, ideally more, may be required for accurate forecasting and reconstruction of these events on timescales shorter than days. Plain Language Summary: We analyze a set of events in which the number of electrons trapped in Earth's outer radiation belts drops rapidly due to inward movement of the outer edge of Earth's magnetic field. These observations are compared to models of the outermost trapped electron orbits derived from models of Earth's magnetic field and particle tracing models. These models of the largest trapped orbits agree well with the losses seen over the timescale of hours but fail to reproduce more rapid decreases in the number of electrons measured on the timescale of minutes. We show that different satellites in geostationary orbit observe different trends in the trapped electron population on timescales of less than a day during geomagnetic storms due to their separation in longitude. These differences demonstrate that data from at least three satellites in geostationary orbit, ideally more, may be required for accurate, high time resolution forecasting and reconstruction of Earth's radiation belts during geomagnetic storms. Key Points: Last closed drift shell models based on TS05 and TS07 fields underpredicted and occasionally overpredicted brief magnetopause crossings Geostationary satellites only 4 hr apart in magnetic local time may see different flux profiles for events with geosynchronous magnetopause crossings Fluxes observed on the nightside may be unrepresentative of dayside conditions showing the need for greater longitudinal satellite coverage